Relationship of mindfulness, emotional intelligence and burnout syndrome in the teaching-learning process: a systematic review - González-Valero, G.; Puertas-Molero, P.; Ramírez-Granizo, I.; Sánchez-Zafra, M.; Ubago-Jiménez, JL. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Emotional intelligence is important in the way emotions are acquired, processed, and regulated. One of the possible psychosocial risks is Burnout syndrome, understood as emotional fatigue. The mindfulness, is a practice that makes us aware of internal events that we feel, where it adopts an attitude of self-acceptance. The aim of this work is to carry out a systematic review that addresses the relationships between emotional intelligence and Burnout syndrome, through the practice of Mindfulness... The search was carried out in the Web of Science, which after applying the inclusion and exclusion criteria obtained a sample of 22 articles between the years 2000-2017. The main conclusions are the close relationship between psychosocial and emotional aspects, since stressful processes differ with emotional intelligence, a fact that is controlled with Mindfulness.